Correction of muscular imbalance for prevention of damages of swimmer's support-locomotory apparatus - Solovjova, J. (Proceedings XII FINA World Congress on sports medicine, April 1997 Göteborg, Sweden, 1997)
Ziel der Studie: Erkennung von Muskelverkürzungen über die Überprüfung der Funktionsfähigkeit der einzelnen Muskeln (nach Yanda). Probanden und Methode: